Impaired Telomere Length and Telomerase Activity in Peripheral Blood Leukocytes and Granulosa Cells in Patients With Biochemical Primary Ovarian Insufficiency. Issue 3 (March 2017) - Xu, Xiaofei; Chen, Xinxia; Zhang, Xiruo; Liu, Yixun; Wang, Zhao; Wang, Peng; Du, Yanzhi; Qin, Yingying; Chen, Zi-Jiang
Abstract : (Abstracted from Hum Reprod 2017:32:201–207) The underlying cause of primary ovarian insufficiency (POI) is unknown in most cases, which generally are referred to as idiopathic. Primary ovarian insufficiency is associated with biological reproductive aging and encompasses 3 stages: occult, biochemical, and overt.